A long‐term experience with expansion of Milan criteria for liver transplant recipients. Issue 6 (1st May 2018) - Commander, Sarah Jane; Shaw, Brian; Washburn, Laura; Yoeli, Dor; Rana, Abbas; Goss, John A.
Abstract: The Milan criteria (MC) have historically determined eligibility for transplantation for hepatocellular carcinoma (HCC). The United Network for Organ Sharing (UNOS) Region 4 expanded the criteria for transplantation in HCC to include a single tumor ≤6 cm or up to 3 tumors with the largest diameter ≤5 cm and total additive diameter ≤9 cm (R4C). The aim of this study was to report the 10‐year outcomes of this expanded criteria compared to MC. Transplants performed for HCC in Region 4 between October 2007 and December 2016 were reviewed using the UNOS database. Recipients were categorized based on imaging findings at initial evaluation. A total of 2068 patients were included in the study. There was no significant difference in 10‐year patient survival between the groups (53% MC vs 48% R4C, P  = .23). There was also no significant difference in recurrence‐free survival (54% MC vs 47% R4C, P  = .15) or allograft survival (53% MC vs 48% R4C, P  = .16). Finally, there was no significant difference in outcomes between the MC and R4C groups when stratifying patients by locoregional therapy. This study demonstrates promising data that the criteria for liver transplantation in HCC can be safely expanded to the R4C without compromising outcomes.